IMPROVEMENT OF TECHNOLOGIES FOR PREPARING FUTURE TEACHERS FOR PROFESSIONAL ACTIVITY BASED ON AN INNOVATIVE APPROACH (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article explores the issues of improving modern mechanisms and innovative technologies for preparing future teachers for professional activities within the higher education system. The research aims to develop an effective model for enhancing students' professional competencies in an innovative educational environment. The study scientifically substantiates the importance of forming creative thinking, digital didactics, and interactive methodical approaches in future specialists. Based on the analysis conducted, practical recommendations and improved technological stages aimed at increasing the pedagogical mastery of future teachers are proposed.